Benefit of Modulated Masking in hearing according to age - Mônyka Ferreira Borges Rocha; Karina Paes Advíncula; Cristiane do Espírito Santo Xavier Simões; Diana Babini Lapa de Albuquerque Britto; Pedro de Lemos Menezes (Brazilian Journal of Otorhinolaryngology)
Objective: To analyze the Benefit of Modulated Masking (BMM) on hearing in young, adult and elderly normal-hearing individuals. Methods: The sample included 60 normal-hearing individuals aged 18–75 years who underwent behavioral assessment (sentence recognition test in the presence of steady and modulated noise) and electrophysiological assessment (cortical Auditory Evoked Potential) to investigate BMM. The results were analyzed comparatively using the paired t-test and ANOVA for repeated measures, followed by the Bonferroni post-hoc test (p-value < 0.05). Results: A decrease in latencies and an increase in amplitudes of cortical components (P1-N1-P2) was observed due to noise modulation in all age groups. Modulated noise generated better auditory threshold responses (electrophysiological and behavioral), compared to steady noise. The elderly presented a higher threshold in both hearing domains, compared to the other participants, as well as a lower BMM magnitude. Conclusion: It was possible to conclude that the modulated noise generated less interference in the magnitude of the neural response (smaller latencies) and in the neural processing time (larger amplitudes) for the speech stimulus in all participants. The higher auditory thresholds (electrophysiological and behavioral) and the lower BMM magnitude observed in the elderly group, even in the face of noise modulation, suggest a lower temporal auditory performance in this population, and may indicate a deficit in the temporal resolution capacity, associated with the process of aging. Level of evidence: 3.